CURRENT STATE AND PROBLEMS OF DEVELOPMENT OF COURIER SERVICES IN UZBEKISTAN (Archive of Conferences, 2021)
The activities of the main postal service of Uzbekistan in recent years have caused concern and dissatisfaction with the leadership of the republic in connection with the deterioration of its main indicators. In the international sphere, the republic also has no indicators. In order to change the situation and reform the activities of the postal service of Uzbekistan, the country's leadership and government have taken a number of decisive measures this year. However, for the successful implementation of reforms, it is advisable to form a digital ecosystem in the national mail of Uzbekistan